Muscle activation patterns at the knee following proprioceptive training - Besier, T. F.; Lloyd, D. G.; Ackland, T. R. (1999)
Due to its lack of bony congruence, the human knee joint must rely on surrounding structures such as muscle and ligaments to maintain joint stability. Little is known about the load sharing properties of muscle and ligaments, however it has been shown that proprioceptive training can reduce the incidence of anterior cruciate ligament injuries (Caraffa et al, 1996). The underlying neural and biomechanical mechanisms behind this training are unknown. It is commonly believed that afferent feedback from mechanoreceptors form a reflex response that activates muscles to protect the joint, or increases the reflex response from a perturbation. Unfortunately, this reflex pathway coupled with an electromechanical delay is too slow to provide any immediate protection to the joint. We hypothesise that this afferent feedback is actually used in a learning response to alter muscle activation strategies in a feed-forward sense. The purpose of this study was to: (a) determine what activation strategies are evident during dynamic tasks that challenge knee joint stability and, (b) induce changes in the muscle strategies with a proprioceptive training protocol. Ten first division soccer players performed running and sidestepping tasks before and after a 3 week wobble board training programme (20 min/day, 4x/wk). The tasks included a straight run, a sidestep to 30o and 60o and a cross-over cut to 30o. Muscle activations (filtered, normalised electromyographic data) were measured from 10 muscles surrounding the knee joint whilst knee joint kinetics and kinematics were determined using a Vicon motion analysis system. Co-contraction of flexors and extensors was evident as a neural strategy used to stabilise the knee joint during tasks that imposed greater varus and valgus load to the knee. Co-contraction was significantly greater for the sidestepping tasks compared to the straight run (p<0.01). Selective muscle activation of medial and lateral muscles was also evident as a strategy to counter the varus/valgus loads experienced during sidestepping tasks. Following the proprioceptive training programme, co-contraction increased by ~20% (p<0.01) with an increase in hamstring and gastrocnemius activation throughout the gait cycle for all tasks. Changes in selective muscle activations were also evident following training with increases in medial and lateral muscle groups to counter valgus and varus loads respectively. These changes suggest that afferent feedback from various mechanoreceptors can be used to alter muscle activations in a feed-forward sense to maintain joint stability and protect the ligaments of the knee joint.